Effect of modified atmosphere packaging (MAP) and gaseous ozone pre-packaging treatment on the physico-chemical, microbiological and sensory quality of small berry fruit. (December 2020) - Pinto, L.; Palma, A.; Cefola, M.; Pace, B.; D'Aquino, S.; Carboni, C.; Baruzzi, F.
Highlights: Comparison of ozone-MAP technology on three small berry fruit quality. Ozone-MAP technology improves small berry fruit microbial quality. Main physico-chemical parameters are not affected by ozone pre-treatment. Ozone-MAP treatment preserved total and individual anthocyanins in blueberries. Abstract: The aim of this work has been to evaluate the combined effect of modified atmosphere packaging (MAP), and a gaseous ozone pre-treatment on the main microbiological and chemical parameters of strawberries, raspberries and blueberries during cold storage. The three types of small fruit were exposed to 13 mg m −3 of gaseous ozone (about 6 ppm) for 16 h at 1 °C (±0.5 °C) and then stored for 15 d under MAP (10 kPa O2 and 40 kPa CO2 ) or in air at 4 °C. The combined technology determined a significant (P ≤ 0.05) reduction of the yeast and mould counts, compared to samples stored in air and MAP without any pre-treatment. The main quality parameters of the three types of fruit were not affected by combined ozone pre-treatment and MAP storage. The combined effects of ozone and MAP led to a better preservation of the total and individual anthocyanins in the blueberries during cold storage. In conclusion, the exposure to gaseous ozone before packaging followed by storage under MAP could be a useful technological approach to extend the postharvest storage of small berry fruit.